VENN DIAGRAM METHOD FOR STUDENTSâ ABILITY IN WRITING AT INTENSIVE ENGLISH CLASS OF UNISMUH MAKASSAR - Junaid, Junaid (EXPOSURE JOURNAL, 2012)
The objectives of this research are to find out the improvement of the studentsâ writing ability in terms of content and organization through Venn Diagram Method at Class A students of Intensive English Class. This research used Classroom Action Research (CAR). It had conducted two cycles. Where each cycle is consisted of four meeting. It employed writing test as instrument. The number subject of the research were 28 students and consist of 5 men and 23 women. Implementation of the first and the second cycle during the four meeting. Technique of the data collection used the cycle, based on the material being taught. Based on the findings of the research, the improvement of the studentsâ writing ability in content and organization were significant improved. Where the mean score in content was 7.79 and mean score in organization was 7.57. Itâs mean that by using Venn Diagram method can improve the studentsâ writing ability.Keywords: Venn Diagram, Method, Writing.Tujuan dari penelitian ini adalah untuk mengetahui peningkatan kemampuan menulis siswa dalam hal konten dan organisasi melalui Metode Diagram Venn Mahasiswa di Kelas A, Intensive English Class. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK). Penelitian ini telah dilakukan dua siklus. Dimana setiap siklus terdiri dari empat pertemuan. Penelitian melibatkan tes menulis sebagai instrumen. Jumlah Subjek penelitian adalah 28 siswa dan terdiri dari 5 laki-laki dan 23 perempuan. Pelaksanaan siklus pertama dan kedua selama empat pertemuan. Teknik pengumpulan data yang digunakan siklus, berdasarkan materi yang diajarkan. Berdasarkan temuan penelitian, peningkatan kemampuan menulis mahasiswa dalam konten dan organisasi yang signifikan ditingkatkan. Dimana nilai rata-rata dalam konten adalah 7.79 dan berarti nilai dalam organisasi adalah 7.57. Ini berarti bahwa dengan menggunakan metode Diagram Venn dapat meningkatkan kemampuan menulis mahasiswa.Kata Kunci: Diagram Venn, Metode, Menulis.